Replications of Two Closely Related Groups of Jumbo Phages Show Different Level of Dependence on Host-encoded RNA Polymerase - Matsui, Takeru; Yoshikawa, Genki; Mihara, Tomoko; Chatchawankanphanich, Orawan; Kawasaki, Takeru; Nakano, Miyako; Fujie, Makoto; Ogata, Hiroyuki; Yamada, Takashi (Frontiers in Microbiology, 2017)
Ralstonia solanacearum phages ϕRP12 and ϕRP31 are jumbo phages isolated in Thailand. Here we show that they exhibit similar virion morphology, genome organization and host range. Genome comparisons as well as phylogenetic and proteomic tree analyses support that they belong to the group of ϕKZ-related phages, with their closest relatives being R. solanacearum phages ϕRSL2 and ϕRSF1. Compared with ϕRSL2 and ϕRSF1, ϕRP12 and ϕRP31 possess larger genomes (ca. 280 kbp, 25% larger). The replication of ϕRP12 and ϕRP31 was not affected by rifampicin treatment (20 µg/ml), suggesting that phage-encoded RNAPs function to start and complete the infection cycle of these phages without the need of host-encoded RNAPs. In contrast, ϕRSL2 and ϕRSF1, encoding the same set of RNAPs, did not produce progeny phages in the presence of rifampicin (5 µg/ml). This observation opens the possibility that some ϕRP12/ϕRP31 factors that are absent in ϕRSL2 and ϕRSF1 are involved in their host-independent transcription.